Factors Influencing Corporate Sustainability Practices And Reporting Among The Developed And Emerging Climes - Gold, Nusirat Ojuolape (2022)
In recent years, the issue of global warming spanning from climate change to the excessive exploitation of natural resources has piqued the interest of people from all walks of life globally. Anthropogenic activities are without a doubt the primary cause of environmental degradation, with majority having direct linkage to corporate activities. Hence, triggering constant pressure from public for companies to reassess their activities and adopt sound sustainability practice. Concerned authorities, such as the government, regulators, and other key stakeholders also have their interest piqued in combating global warming and other harmful environmental issues. As a result, numerous efforts were created, one of which resulted in the carbon pricing policy, a means to curb greenhouse gases (GHG) emission. Although, some companies had begun implementing sustainability strategies into their management processes, yet response rate is still not encouraging as report showed the number of companies with actual sustainability practice is far below the number of companies that claim to have adopt sustainable practice and reporting. As a result, it becomes more imperative to delve into factors that can influence firms to embrace extensive sustainability practice and reporting in the world at large.